Technology-Based Community Service: Application of Oil Palm Midrib Stick Shaving Machine to Empower Local Creative Economy in Tebing Linggahara Village - Fadilah Zamzami, Lutfi; Septyani, Ika Ayu Putri; Asnora, Fadzil Hanafi (Majalah Ilmiah UPI YPTK, 2025)
This program introduced a stick shaving machine as a solution, aiming to help local craftsmen work faster, reduce physical strain, and expand production capacity. More than just providing a tool, the program also offered training and mentoring so that the community could maximize its use. In this way, the initiative not only tackled technical issues but also empowered the community to develop their creative economy sustainably. The program directly contributed to the community by providing a stick-making machine that enabled craftsmen to increase productivity, reduce physical workload, and transition toward a more efficient production process. It also encouraged knowledge sharing and stronger collaboration among local residents. The activities included field observation, interviews, training sessions, and hands-on practice with the machine. These steps allowed participants to identify production challenges, adopt new technology, and compare its outcomes with traditional manual methods. The adoption of the machine increased daily production capacity by more than 50%, shortened processing time, and minimized fatigue. Furthermore, the community experienced more consistent marketing through local agents, creating a stronger link between production and distribution. The introduction of the oil palm midrib stick-making machine proved effective in optimizing the village’s agroindustrial potential and achieved the program’s objective of strengthening the creative economy. This initiative not only improved household income but also provided a practical and sustainable model of community empowerment based on local agricultural resources.